A numerical study of design and off-design operations of SHM1 airfoil - Sengupta, Aditi; Guha, Abhijeet (Frontiers in Aerospace Engineering, 2025)
Natural laminar flow airfoils are essential technologies designed to reduce drag and significantly enhance aerodynamic performance. A notable example is the SHM1 airfoil, created to meet the requirements of the small-business jet by Honda R&D. This airfoil has undergone extensive testing across various operational conditions, including low-speed wind tunnel tests and flight tests across a range of Reynolds numbers and free-stream Mach numbers. Additionally, investigations into drag-divergence behavior have been conducted using a transonic wind tunnel, with subsequent studies focusing on transonic shock boundary layer interactions through both experimental and numerical approaches. This study employs a series of numerical simulations to analyze the flow physics and aerodynamic performance across different free-stream Mach numbers in the subsonic and transonic regimes. The analysis offers a comprehensive overview of the aerodynamic performance by making use of instantaneous and time-averaged load and pressure distributions, highlighting the different flow structures (trailing edge vortices, Kutta waves, shock waves - both normal and oblique) and associated time scales in the unsteady flow field and how these impact the performance and extent of separated flow on the SHM1 airfoil. This is achieved by examining computed instantaneous numerical Schlieren for various design conditions (such as low speed, climb, and cruise) and off-design scenarios (including transonic shock emergence, drag-divergence, and shock-induced separation). The dominant time scales, the time-averaged load distributions and boundary layer parameters are compared to provide a comprehensive overview of the SHM1’s aerodynamics, establishing benchmark results for optimization of various flow separation and shock control techniques.